Working for the Lakota: the theory of participation - Brydge, Michael, author; Sherman, Kathleen Pickering, advisor; Leisz, Stephen J., committee member; Ishiwata, Eric, committee member (Colorado State University. Libraries, 2012)
This study is about a community and a process. It conveys the importance of participatory approaches to engage locally initiated, community development. Community members and outsiders alike have a place in development through entering the process as participants, focused on locally driven processes. After discussing colonial modes of development, a 2011 youth building initiative, from the Pine Ridge Indian Reservation, South Dakota, is discussed as a mode of decolonization by Lakota communities. Participatory development processes, from the initiative, provide examples of how participation is useful, both for development in the 'here and now', and to test and improve the theory of participation.
Keywords: community development; indigenous development; Lakota empowerment; participation; participatory development; youth development